Variable executive remuneration and company performance : insights from the Johannesburg Stock Exchange, South Africa - Padia, Nirupa; Naik, Minal; Callaghan, Chris W. (Acta commercii, 2020)
Orientation: Agency theory predicts that agency relationships are subject to the principalagent problem. Other theories also suggest that executives may tend to maximise sales revenues, or expand their spans of influence through growth, at the expense of the net value of the firm or its profitability. Research purpose: The purpose of this study is to test which forms of company performance are associated with higher executive variable pay ratios or determine the proportion of variable director remuneration to total remuneration. Motivation for the study: The extent to which variable remuneration is associated with different types of firm performance is unclear. Research design, approach and method: This study applies a simple panel regression model to test the extent to which the variable ratio of total director remuneration contributes differently to increases in firm revenue, total assets, return on assets, or measures of Tobin’s Q. These relationships are tested for listed companies on South Africa’s Johannesburg Stock Exchange, South Africa, for the years 2011–2014. Main findings: Variable remuneration is found to be negatively and strongly related to total revenue and negatively and weakly related to total assets (the gross measures of performance). In contrast, variable remuneration is weakly and positively related to Tobin’s Q, a measure which better reflects the interests of shareholders than gross measures. Practical/managerial implications: Firms in this context should seek to strengthen the linkages between variable remuneration and forms of performance that reflect the interests of stakeholders. Contribution/value-add: In the wake of global and local governance failures, this study suggests that the use of the variable component of executive remuneration might be helpful in aligning stakeholder interests. Further research might seek to better understand the causal mechanisms that underlie these findings.